Estudo sobre a ação antibacteriana do óleo de melaleuca no controle de microrganismos causadores da mastite bovina - Micketen, Renata (2024)
Bovine mastitis is an inflammation of the mammary glands and is one of the most common and harmful diseases that affect milk production in cattle. Pathogenic bacteria are often responsible for the development of this disease. In this context, the present study aims to investigate the antibacterial activity of tea tree oil against the main bacteria that cause bovine mastitis. To evaluate the effectiveness of tea tree oil as a potential antibacterial agent, the Disk Diffusion Test, Minimum Inhibitory Concentration Test (MIC) and Minimum Bactericidal Concentration (MBC) were performed. In the disk diffusion test, paper disks soaked with tea tree oil were used and placed on a Petri dish containing Muller Hinton agar inoculated with the bacterial cultures of interest. After the incubation period, it was possible to observe the formation of zones of bacterial growth inhibition around the discs. The diameter of these zones was measured and used as an indication of the antibacterial activity of tea tree oil. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests were carried out to determine the lowest concentration of tea tree oil capable of inhibiting bacterial growth and concentration capable of killing bacteria. For this test, dilutions ranging in concentrations from 4 to 0.03% of tea tree oil in Muller Hinton broth were prepared. ATCC reference strains and bacteria isolated from milk from cows with mastitis were inoculated in each dilution. After the incubation period, there was the lowest concentration of tea tree oil in which there was no visible bacterial growth. In the qualitative disk diffusion test, it was possible to observe the formation of inhibition halos, confirming the bacterial susceptibility of tea tree oil. In the MIC and MBC tests, concentrations capable of inhibiting bacterial development ranged from 2 to 0.1% and the CBM ranged from 2 to 0.5%. The results obtained provided important information about the antibacterial activity of tea tree oil against bacteria that cause bovine mastitis. Contributing to the development of alternative therapies for the prevention and treatment of bovine mastitis, reducing dependence on conventional antibiotics.